Nature+ in India: Soil Baseline in India - Kaushal, Manoj; Gebrehawaryat, Yosef; Fadda, Carlo (2024)
Soil health is a crucial factor for agriculture, supporting crop growth and determining productivity. Baseline data on soil properties helps in effective land management and sustainable agricultural practices. To understand and guide sustainable agricultural practices and soil management strategies, a soil baseline study is conducted by Alliance Scientists and partners in 2024 in two locations Akole and Nandurbar of Maharashtra state, India. Akole and Nandurbar are regions located in the western part of Maharashtra, India, within the hilly terrains of the Sahyadri mountain range. These areas are known for their agricultural activities, with diverse crops grown in varying topographies. However, like many other regions of India, these areas also face challenges related to soil health, fertility, and sustainable management practices. The soils in Akole and Nandurbar are primarily black soils, which are rich in clay content and ideal for growing crops like cotton, soybean, and groundnut. These soils are known for their moisture retention capacity but can become compacted and prone to waterlogging under certain conditions.